Supporting the Development of the Perceived and Actual Research Competence of Pre-Service Teachers - Miha Matjašič; Janez Vogrinc (Education Sciences, 2025)
The aim of this study was to investigate the development of the perceived and actual research competence of pre-service teachers enrolled in a master’s programme using a pre-test–post-test research design. Research competence, which encompasses a range of knowledge, skills, and attitudes and includes both perceived (self-reported) and actual (objective) concepts, is critical for effective teaching, teacher professional development, and the integration of research-based practises into the classroom. The study examined how perceived research competence, as measured by a web questionnaire, changed over the course of the semester and how these changes corresponded to actual research competence as measured by the knowledge test. The participants were pre-service teachers from the University of Ljubljana who completed both the web questionnaire and the knowledge test at two time intervals during a research-based course. The results indicate a significant increase in perceived research competence, especially in terms of research knowledge and skills, as well as a significant improvement in actual research competence. While there was a statistically significant increase in positive attitudes towards research, this increase was moderate. This study also emphasises the alignment between perceived and actual research competence over time, suggesting that practical research experiences help students to develop more realistic self-assessments. By furthering the understanding of how research competence develops over time, this study provides actionable insights for the design of more effective research-based teaching.